Техніко-типологічний аналіз археологічних матеріалів палеолітичної стоянки Галич ІI - Ситник, О.; Коропецький, Р.; Богуцький, А.; Ланчонт, М.; Мадейська, Т. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Paleolithic expedition of I. Krypiakevych Institute of Ukrainian studies of NAS of Ukraine (led by O. Sytnyk) in 2002 and 2004 carried out excavations of Paleolithic site Halych II. Area about 64 square meters was explored. Cultural horizon (not in-situ) was found on the depth 4–6 meters from surface. 265 flint artifacts were collected. In technical aspect prismatic cores and blades dominate. In typological – burins, blades, retouched flakes and side-scrappers. Numerous collection of bones’ remains (generally, mammoth’s) were found there too. Flint inventory can be dated back to first half of Upper Paleolithic and it belongs to Gravettian culture. On sounding, situated from 20–30 meters westward from excavated territory, about 30 flint artifacts were found. Geological deposits, which consist this collection, are dated to periods amersfoort and brorup. Technologically, collected materials can be determined as Micoquian.